Wyobraźnia pedagogiczna. Źródła interdyscyplinarne i zarys koncepcji - Drozdowicz, Jarema (My University, 2021)
The paper explores the concept of pedagogical imagination in relation to three major sources of theoretical influence – ethnography, sociology and history. It makes the attempt to combine them and investigate how the notion of imagination might be used in pedagogy and the study of education in general. It raises the issue of subjectivity and puts it in the context of emergence of new forms of qualitative analysis in contemporary pedagogy. This new form of scientific inquiry and new analytical questions that arise along are related to the problem of experience. The paper also makes an attempt to highlight the significance of experience in gaining a deeper insight into the ways people shape their own educational experiences. When speaking of experience in the educational space, especially within the school reality, we might point out the subjectified forms of participation in those areas of public life. The stressed out in the text and combining mentioned types of imagination forms of living the participation in what is usually objectified and institutionalized field of education, upbringing, schooling systems and various educational policies implemented in schools requires nevertheless a critical approach towards the effects of functioning of those domains in the social praxis, a step which is typical for the aforementioned disciplines. To paraphrase Bruno Latour, today we need to reformulate what is social in the categories typical to the emic analysis natural to ethnography rather than to sciences which use tools promising maximum objective insight into reality.
Pedagogical imagination. Interdisciplinary sources and an outline of the concept
Keywords: pedagogical imagination; sociological imagination; ethnographic imagination; historical imagination; qualitative research